Growth of Infants on Exclusive Breastfeeding up to 6 Months and then along with Complementary Feeding in a Hospital Based Survey - Gupta, BK (Journal of Universal College of Medical Sciences, 2013)
OBJECTIVE: To study growth of infants on exculsive breastfeeding for 6 months and further along with complementary feeding upto 12 months of age. METHODS: This Cross-sectional, Prospective, Hospital Based, Observational study was conducted in Department of Pediatrics, in collaboration with the Department of Gynaecology and Obstetrics, Universal College of Medical Sciences-Teaching Hospital, Bhairahawa, Lumbini, NEPAL on 292 infants born at the hospital and their growth monitored over a period of 12 months. Evaluation of nutritional trends practiced by the people and its effects on growth of infants was done and compared to the growth of infants according to the NCHS-WHO (CDC-2000) standards. RESULTS: The average weight at birth and average weight- for- age for both male and female infants were lower th than the 50 perentile of National Center for Health Statistic (NCHS) standards. The average length of the th infants was found lower than 50 percentile curve of NCHS. The difference of length between boys and girls was th insignificant at 6 months (Z<1.88). The average head circumference in our study was below 50 percentile of NCHS standard. The difference between weight, length, mid arm and head circumference of boys and girls was insignificant at 6, 9, 12 months (Z<1.88). CONCLUSIONS: Most of the values represent normal growth but the gain in weight and length of infants was th far below the 50 percentile of NCHS-WHO standards. DOI: http://dx.doi.org/10.3126/jucms.v1i2.8404 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 13-19